Analysis Of The Management Of Medicine Supply Needs At Puskesmas Seberang Padang In Padang City - Ratih Wijaya Isardi; Gesit Thabrani (Journal of Economics, Management and Accounting (JEMA), 2024)
This study aims to determine the management of medicine supply needs at Puskesmas Seberang Padang and the actions taken by Puskesmas Seberang Padang in overcoming the shortage of medicine supply needs.This research includes research with a qualitative approach using primary data, directly from the original source through interviews, observation and documentation to the research site. The data analysis technique uses the Miles & Huberman model.The results showed that in managing the supply of medicine needs, Puskesmas Seberang Padang has carried out planning and procurement. However, the main theory used by researchers cannot be implemented optimally at the Puskesmas Seberan Padang. Because the purpose of the planning carried out by Puskesmas Seberang Padang is to estimate the type and amount of medicine that are close to the needs and based on the budget. Whereas in Supply Chain Management (SCM) planning is carried out to predict and control supply needs and maximize company surplus to minimize additional costs used to purchase supplies on a small basis. When procurement is carried out by Puskesmas Seberang Padang to suppliers, it does not use supplier strategies and criteria. This is due to the urgency of medicine supply needs. So that PPTK employees ask for the type and amount of medicine to all suppliers with the provision of fast delivery. With the aim of minimizing the occurrence of medicine vacancies.